Aplikasi Computer Assisted Test (CAT) Pada Penerimaan Mahasiswa Baru Sekolah Tinggi Teknologi Pagar Alam (STTP) - Ferry Putrawansyah (Ikatan Ahli Informatika Indonesia (IAII), 2017)
This study aims to develop a valid and practical Computer Assisted Test (CAT) Application. This research is based on a less-than-optimal test process because it still uses paper sheets and the graduation announcement process waiting for a long time. The instrument used in this study is the expert review to test the validity and test of one-to-one to know the practicality. Based on the Expert Review results, this product is stated as valid from the average value of the assessment of media experts, design experts, and evaluation experts with a score of 3, 9, so the product category is valid. Then the practicality of this product was assessed by three respondents with an average score of 3.9 with practical criteria and so based on the CAT application product that is valid and practical. Then suggested to the next researcher to be able to research the Android operating system.